Morebitni medsebojni vpliv prozodije slovenskega govora in slovenske ljudske pesmi - Rebernik, Teja (Slavistična revija, 2017)
The article tackles the popular topic of the potential interaction of music and language by comparing the prosody of Slovene speech and the melodic and rhythmic properties of the Slovene folk song. The study shows potential connections between tonemicity and interval range, the predictability of word stress and rhythmic accent, and different dialects and their musical traditions. The article thus presents a preliminary study of potential similarities between a specific language and music. Although, due to a lack of research for other languages, it is difficult to guarantee that the results are not coincidental, the study presents a promising first attempt at such a comparison.
Keywords: prozodija; Slovene; Slovene dialects; Slovene literature; slovenska književnost; slovenska ljudska glasba; slovenska narečja; slovenske ljudske pesmi; slovenščina; tonematika